Fluorescent imaging of endothelial glycocalyx layer with wheat germ agglutinin using intravital microscopy. Issue 1 (19th November 2015) - Kataoka, Hanae; Ushiyama, Akira; Kawakami, Hayato; Akimoto, Yoshihiro; Matsubara, Sachie; Iijima, Takehiko
Abstract : Endothelial glycocalyx (GCX) is located on the apical surface of vascular endothelial cells and is composed of a negatively‐charged network of proteoglycans and glycoproteins. The GCX plays an important role in maintaining the integrity of vascular walls and preventing leakage of plasma. Therefore, degradation of the GCX is believed to lead to pathological leakage of plasma. Because the GCX is a very thin layer, its ultrastructural image has been demonstrated on electron microscope. To explore the function of the GCX, it should be visualized by a microscope in vivo. Thus, we developed in vivo visualization technique of the GCX under fluorescence microscopy using a mouse dorsal skinfold chamber (DSC) model. To label and visualize the GCX, we used fluorescein isothiocyanate (FITC)‐labeled lectin, which has a high specificity for sugar moieties. We examined the affinity of the different lectins to epivascular regions under an intravital fluorescent microscope. Among seven different lectins we examined, FITC labeled Triticum vulgaris (wheat germ) agglutinin (WGA) delineated the GCX most clearly. Binding of WGA to the GCX was inhibited by chitin hydrolysate, which contained WGA‐binding polysaccharide chains. Furthermore, the septic condition attenuated this structure, suggesting structural degradation of endothelial GCX layer. In conclusion, FITC‐labeled WGA lectin enabled visualization of endothelial GCX under in vivo fluorescence microscopy. Microsc. Res. Tech. 79:31–37, 2016 . © 2015 Wiley Periodicals, Inc.